Optimization of hydraulic fracturing treatment parameters to maximize economic benefit in tight oil. (1st December 2022) - Xu, Shiqian; Guo, Jianchun; Feng, Qihong; Ren, Guotong; Li, Yuyao; Wang, Sen
Highlights: Fracturing treatment parameters were optimized to maximize economic benefit. Nonlinear flow, dynamic capillary pressure and natural fractures were considered. Induced secondary fractures were modeled using continuum damage model. Pursuing uniform propagation or maximum SRV may not obtain the highest NPV. Optimization surfaces for four types of tight oil reservoirs are constructed. Abstract: The optimizations of hydraulic fracturing treatment parameters are widely studied. Three optimization goals are usually pursued, i.e., uniform fracture propagation, stimulated reservoir volume (SRV) or fracture area maximization, and economic benefit maximization. However, when we pursue uniform fracture propagation or SRV maximization, can we also obtain the maximum economic benefit? Since the simulation of fracturing and production are usually-two separate methods, few studies have simultaneously investigated the relationship between fracturing treatment parameters and these three optimization goals. Therefore, the novelty of this work is that these relationships are systematically revealed under four different geological conditions, i.e., homogeneous and heterogeneous properties, hydraulic fracture turning, and induced secondary fractures. In comparison with previous hydro-mechanical model, our model can not only simultaneously simulate fracturing and production, but also consider some characteristics of tight oil reservoir, including nonlinear flow in tight matrix, dynamic capillary pressure, hydraulic fracture turning, and induced secondary fractures. Furthermore, simulation results of orthogonal experimental design are applied to fit 3D surfaces showing the relationship between fracturing treatment parameters and net present value (NPV). These 3D surfaces provide optimal fracturing treatment parameters. The results indicate that, in homogeneous reservoirs, pursuing uniform fracture propagation or maximum fracture area can obtain the highest NPV. However, in heterogeneous, hydraulic fracture turning, and induced secondary fracture cases, pursuing uniform propagation or maximum SRV usually cannot obtain the highest NPV. Our models serve as very useful tools for optimizing fracturing treatment parameters in different types of tight oil reservoirs, which play an increasingly significant role in the improving economic benefit of tight oil development.